Estudo das propriedades anticâncer da piplartina - Bezerra, Daniel Pereira (2008)
Piplartine is a known alkaloid/amide from Piper species with interesting cytotoxic properties. In order to understand the antineoplasic potential of piplartine, a pharmacological study was performed in several biological models. Piplartine displayed potent cytotoxicity against all cancer cell lines. By comparing the cytotoxicity of selected molecules that differ in structural elements, it was identified that the presence of the α,β-unsaturated carbonyl moiety of the amide ring is an important structural requirement for cytotoxic activity. In healthy peripheral blood mononuclear cells exposed to piplartine, it was observed only weak cytotoxic activity. Moreover, piplartine treatment induced apoptosis in HL-60 cells, by the intrinsic pathway, in a dose-dependent manner, as observed by morphology and cytoplasmatic membrane integrate changes, alteration in mitochondrial membrane potential and an increase in internucleosomal DNA fragmentation. In the cell cycle analysis, piplartine induced G2 cell cycle arrest. Piplartine treatment induced DNA strand breaks in V79 cells, as detected by neutral and alkaline comet assay. Its genotoxic mechanism of action seems to be similar to its cytotoxic activity. No mutagenic effect, with or without metabolic activation (S9 mix), in Salmonella strains (prokaryotic model) was observed under experimental conditions. On the other hand, piplartine was mutagenic and recombinogenic in Saccharomyces cerevisiae assays (eukaryotic model). This can be explained due to the differences in physiological between eukaryote and prokaryote DNA topoisomerase II, reflecting a possible interference of piplartine upon this enzyme activity. In vivo micronucleus test, piplartine increased in the levels of micronuclei in the highest dose tested (100 mg/kg). Nevertheless, no bone marrow cytotoxicity was found after piplartine-treated animals as observed by the polychromatic/normochromatic erythrocyte ratio. In pharmacokinetic study, a LC–MS/MS bioanalytical method for the determination of piplartine in rat plasma was established. The method developed shows great linearity and low quantification limit; precision and accuracy were within the acceptable ranges for bioanalytical purposes. In the concentration–time profiles, piplartine showed absorption kinetic of a monocompartimental model. Additionally, the plasma levels are compatible with the in vitro cytotoxicity which leads us to propose that the anticancer activity of piplartine is due to its direct cytotoxic properties. In antitumor assay, the combination of piplartine with 5-fluourouracil led to an in vitro and in vivo increasing of the tumor growth inhibition. In addition, hematological analysis showed leukopenia after 5-fluourouracil treatment, which was reversed by the combined use of piplartine. These data suggest that piplartine has promising anticancer potential